Growing presence of real options in global financial markets - Kensinger, John W. (Research in finance,, 2017)
Research in Finance seeks to provide a collection of quality research articles that reflect the current and primary issues in financial markets. Contributions include finance theory and financial practice, plus accounting issues such as reporting derivatives positions, reflecting intangible holdings, or predicting financial distress. The broad theme of this volume of Research in Finance is Comparing the Influence upon Equity Valuation of Strategy Compared with Cash Flow Expectations. Contributions assess the strong role of strategy in equity valuation, compared with valuation of expected dividends. We also see new evidence about the triggers for financial distress in emerging countries.